Vegetation response to Holocene climate change in East Asian monsoon-margin region - Zhao, Yan; Yu, Zicheng (Earth-science reviews, 2012)
Fossil pollen records from 20 sites with reliable chronologies and high-resolution data in the East Asian monsoon margin region were synthesized to document Holocene vegetation and climate change and to understand the large-scale controls. The vegetation experienced different changes over the Holocene in various sub-regions. (1) Near the boundary between modern forest and temperate steppe in Northeast China, forest showed clear expansion in the middle Holocene. (2) In central China near the boundary between steppe/forest and desert, vegetation showed various patterns at different sites. (3) Further west on the Tibetan Plateau near the boundary between highland meadow/steppe and semi-desert/desert, forest expanded at most sites during the early and middle Holocene. Our synthesis indicates that climate in the margin region was slightly moist in the early Holocene, wettest in the middle Holocene, and dry in the late Holocene, though there are regional differences as reflected by vegetation change. This general pattern is very different from either monsoon- or westerly-dominated regions. The maximum moisture occurred during the early Holocene in the monsoon region, while the arid central Asia dominated by the westerlies was driest in the early Holocene and wettest in the mid-Holocene. The interplay of the Asian summer monsoon, westerlies, topography and regional vegetation factors might have contributed to this spatial complexity.